EXPLORING HUMAN RESOURCE DEVELOPMENT IN SERDANG WETAN TOURISM VILLAGE, TANGERANG REGENCY - Kristiana, Yustisia; Mulyono, Stephanie Theodora; Julita, Julita; Nainggolan, Rebecca Faustine (LPSDI Bina Patria, 2025)
Serdang Wetan Tourism Village, located in Legok District, Tangerang Regency, although it has great potential, this village faces challenges in tourism development, especially human resource development. The aim of this research is to identify threats to human resource development and analyze human resource development strategies in the Serdang Wetan Tourism Village. Findings show that low skills in tourism management, low community participation, and limited institutional support hinder tourism development. Improvement strategies include tailored training programs, empowering Tourism Awareness Groups (Pokdarwis), fostering collaboration with educational institutions, and utilizing digital marketing tools. This research underlines the importance of participatory and community-based human resource development in achieving tourism growth and increasing the competitiveness of villages as tourist attractions.